The influence of the fuel spray structure and dynamics of its formation on surface combustion of biofuels in diesel engines - Kulmankov, Sergey P.; Lebedevas, Sergejus; Sinitsyn, Vladimir; Lebedeva, Galina; Kulmankov, Sergey S.; Yakovlev, Sergey (Transport, 2016)
The paper presents the results of the experimental investigation of the structure of the fuel, rapeseed oil and diesel fuel sprays obtained by analysing their optical density. The results are obtained by investigating a conventionally designed fuel supply system and a high-pressure common rail system. The experimental data on the velocity and length of fuel sprays are given. The study has shown that when high pressure fuel supply systems are used, the fuel spray is increased by about three times, while its area is increased up to 50% and homogeneity is also higher. As a result, selfignition delay time is reduced and the combustion process is intensified. The methods, taking into consideration the specific character of using the alternative types of fuel and high pressure systems, which have been tested in the experimental conditions, are suggested for calculating the time of self-ignition delay. The applied methods allow us to reduce the error of determining self-ignition delay time up to five percent. Based on the calculated data, the factors limiting the ignition of the sprayed fuel have been defined.First published online: 27 Jul 2015